Studying the Relationship between Factors related to Stress and Stress Management of Insurance Employees of Iran Social Security Organization - Shojaeian, Reza (2020)
Introduction & Purpose: Considering the stressors in the Social Security Organization and the management of these factors in order to improve efficiency and quality of medical services, the present study aimed to to provide a stress management model for insurance employees of the Social Security Organization of Iran. Materials and Methods: This research is applied in purpose and is survey in method. The statistical population consisted of three groups: Experts familiar with the field of employee stress management that by selective non-random sampling method, 15 individuals were selected. Results: All employees and managers of the Social Security Organization of Iran that 462 were selected based on the Cochran's formula, and 232 people were selected by stratified random sampling method appropriate to the size of the population. In this study, a questionnaire was used to collect the required data. The model design and approval questionnaire with 29 components and indicators was changed to 24 items after obtaining the opinion of experts using the Delphi method. The Stress-Related Factors Questionnaire included 72 questions and the Stress Management Questionnaire consisted of 24 questions. In this study, the content validity of the questionnaire of factors related to stress and stress management were 0.915 and 0.921 respectively, and their reliability was calculated to be 99.1 and 94.6, which was greater than 0.7 and it was acceptable. Data analysis was performed using structural equation modeling with Lisrel software. Discussion: At 5% level error between individual factors (-0.33), occupational factors (-0.37), managerial factors (-5.99), organizational factors (-4.62), environmental factors (0.76 0), there was a significant and inverse relationship between stress and stress management of insurance employees of the Social Security Organization of Iran. Conclusion: The existing facts in the discussion of psychopathology and mental health in the workplace show that a significant percentage of the causes of mental illness and work fatigue among the employees of organizations can be found in the behavior methods and personality of managers.